Nietzsche's View of Socrates - Dannhauser, Werner J. (Cornell University Press, 2019)
Clarifying a crucial aspect of Nietzsche's work-his constant preoccupation with Socrates-this intensive study also provides a general introduction to the philosophy of an important and difficult thinker. Through close analyses of two of his major books, The Birth of Tragedy and Twilight of the Idols, as well as his other writings, Professor Dannhauser rescues Nietzsche's thought from the vague generalities that it has too often provoked. His book will be especially valued as a judicious presentation of the quarrel between modern and ancient philosophy. While he makes clear his admiration for Nietzsche, he expresses his doubts that Nietzsche "won" his debate with Socrates.